Pengujian Usabilitas Sistem Pencatatan Transaksi Distribusi Cabai Berbasis Blockchain dengan Cognitive Walkthrough - Rizal Fajar Bancin; Meuthia Rachmaniah (Departemen Ilmu Komputer, Institut Pertanian Bogor, 2022)
Developed software applications should experience user acceptance tests using usability testing. We have developed a blockchain-based chili distribution transaction application but lack usability testing. Usability testing aims to identify and fix flaws in the application before it is released. The method employed was the cognitive walkthrough method using five usability test components to find out how easy it is for new users to use the system. These are application learning ability, efficiency, recall ability, error, and user satisfaction. The test evaluators (respondents) are four supply chain actors: producers, collectors, wholesalers, and chili retailers. The evaluators consisted of ten men and two women, aged 34-39 years, with infrequent laptop use (4-9 times per month). The fastest time for evaluation is for the retail traders (197 seconds), and the delinquent time is for the collectors (275 seconds). At the same time, the average value of the five components of the usability test is 2.73 on a scale of 1.00-3.00. The conclusion obtained is that the applications tested are outstanding, hence ready to be released. Researchers recommend shortened response time to the application. Future research is to develop mobile phones application, which respondents are already familiar with, compared to using applications on laptops.